Transition in, Transition out : a sustainable model to engage first year students in learning : a Practice Report. - Chester, Andrea; Burton, Lorelle; Xenos, Sophia; Elgar, Karen; Denny, Bianca (International Journal of the First Year in Higher Education v.4 n.2 p.125-130 https://doi.org/10.5204/intjfyhe.v4i2.174, 2013)
Peer mentoring, presented as an inclusive teaching approach embedded in the curriculum, has been successfully implemented to support first-year student learning. Developing sustainable and scalable models for large first-year cohorts, however, provides a challenge. The Transition in, Transition out model is a sustainable peer mentoring model supporting the transition of both first and final-year students. The model has been implemented in two Australian psychology programs, one face-to-face and one delivered online. The focus in this Practice Report is on the outcome data for on-campus first-year students at one university. Participants were 231 first-year students (166 females and 65 males). Results suggest positive changes in academic performance and learning approaches as well as positive endorsement of the model. [Author abstract]